2017
DOI: 10.1007/s11356-017-9888-2
|View full text |Cite
|
Sign up to set email alerts
|

Role of illumination intensity in microcystin development using Microcystis aeruginosa as the model algae

Abstract: Microcystis aeruginosa (M. aeruginosa) is one of the most common genera of cyanobacteria in algal blooms. In the present work, the impact of the illumination intensity on the growth of M. aeruginosa has been studied and a grinding method for the extraction of intracellular microcystins (MCs) was developed. The variations of algal density, pH, total phosphorus (TP), and total nitrogen (TN) have been investigated during MCs' culturing period. Results showed that the extraction efficiency of MC-YR by the grinding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 37 publications
2
4
0
Order By: Relevance
“…This study found that during the growth of M. aeruginosa, the pH value of the algal culture increased rapidly with a slight increase in algal density before reaching the maximum value (Fig. 3b), which was also observed by Liu et al (2017). Before reaching the highest pH value, the pH value of Synechococcus increased rapidly to approximately 9.6 with a slight increase in biomass (Bundeleva et al 2014).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…This study found that during the growth of M. aeruginosa, the pH value of the algal culture increased rapidly with a slight increase in algal density before reaching the maximum value (Fig. 3b), which was also observed by Liu et al (2017). Before reaching the highest pH value, the pH value of Synechococcus increased rapidly to approximately 9.6 with a slight increase in biomass (Bundeleva et al 2014).…”
Section: Discussionsupporting
confidence: 63%
“…3a), which may be due to the buffering capacity of algae in response to the pH value of water. When the environmental pH is not conducive to the growth of algae, its self-adaptability enables it to adjust the pH value of the water to be suitable for its growth through a series of physiological and biochemical reactions (Liu et al 2017;Wei et al 2020). However, in this study, M. aeruginosa was unable to exchange substances freely with the outside world in a quite narrow and enclosed environment, and the self-regulation and buffer capacity of the culture environment were relatively weak.…”
Section: Discussionmentioning
confidence: 66%
“…The increase in water pH reduces the content of CO 2 , which is easily absorbed by algae, and HCO This study found that during the growth of M. aeruginosa, the pH value of the algal culture increased rapidly with a slight increase in algal density before reaching the maximum value (Fig. 3b), which was also observed by Liu et al (2017). Before reaching the highest pH value, the pH value of Synechococcus increased rapidly to approximately 9.6 with a slight increase in biomass (Bundeleva et al 2014).…”
Section: Discussionsupporting
confidence: 69%
“…These ndings proved the credibility of the previous speculation that pH uctuations are associated with photosynthesis and inorganic carbons. However, the mechanism of the short-term uctuation still needs further study; that is, the pH values of algal cultures always rise and fall irregularly over 24 h. (2017) found that the density of M. aeruginosa was higher when the environmental pH value was 9.2-10.5, Liu et al (2017) determined that the optimal growth pH range of M. aeruginosa was 7.5 to 10.5, and Chandra and Rajashekhar (2016) found that M. aeruginosa could grow at high alkaline pH (9.0-10.0). These results are consistent with our experimental results; that is, the optimal pH value for the proliferation of M. aeruginosa was 9.56 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Illumination has a significant impact on the growth of microalgae . To find whether illumination would also affect the algicidal ability of the Sp34 supernatant against M. aeruginosa DCM4, the algicidal ratio under full light (24‐h light), light and dark cycle (14:10 h) and dark (0‐h light) conditions were examined.…”
Section: Resultsmentioning
confidence: 99%